LOCAL GUIDELINES FOR DRUG TREATMENT OF PATIENTS WITH COVID-19: LOCAL GUIDELINES FOR DRUG TREATMENT OF PATIENTS WITH COVID-19 - Janković, Slobodan; Pavlović, Katarina; Vukićević, Vladimir; Gavrilović, Jagoda; Folić, Marko M.; Čanović, Predrag; Marjanović, Ružica; Mojsilović, Slavica; Stevanović, Nebojša; Rosić, Nikola (Medicinski časopis, 2020)
Objective. Until now, there have been no guidelines for the use of drugs in patients with COVID 19 in the Republic of Serbia that have been authorized and published in the professional or scientific literature, or on the official websites of the Ministry of Health or health care institutions. The aim of this paper is to present a local guideline for the use of drugs in patients with COVID 19 and the process of its development and adoption.Methods. The guideline proposal was prepared by a working group based on the results of a systematic search of the medical literature, and quality control of found publications from the category “clinical practice guidelines”. The proposal of the working group was considered and adopted at the sessions of the Drug / Therapeutics Committee and the Quality Assurance Committee of the University Clinical Centre Kragujevac.Results. The guideline's recommendations are based on the type of patient, and all have the same degree of recommendation and the same quality of evidence on which they are based. Patient types are formed according to the severity of the disease and the need for respiratory support, as well as according to the risk of secondary bacterial infection.Conclusion. The local guideline to the use of drugs in patients with COVID 19 was developed and adopted in a short period of time, primarily due to the need for its urgent use. Revision of this guide is planned after 6 months from the moment of adoption.